2020
DOI: 10.2147/ppa.s247013
|View full text |Cite
|
Sign up to set email alerts
|

<p>Medication Evaluation in Portuguese Elderly Patients According to Beers, STOPP/START Criteria and EU(7)-PIM List – An Exploratory Study</p>

Abstract: Purpose: The increase in drug prescription for the elderly raises the risk of the occurrence of potentially inappropriate medications (PIMs), thus increasing the incidence of drug-related problems. Likewise, potential prescribing omissions (PPOs) are also highly prevalent in the elderly. This study aimed at assessing the prevalence of PIMs in the elderly by using the EU (7)-PIM list, STOPP criteria version 2 and the Beers criteria version 2015, as well as the prevalence of PPOs by applying the START criteria v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
4
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 46 publications
6
27
4
3
Order By: Relevance
“…An important finding of this study is that the most frequent active principles as PIMs, which were PPIs and BZDs, were present in almost half (46.6%) of the patients, suggesting that actions focused on deprescribing these medications may have a large impact on reducing PIP and, therefore, undesired negative outcomes. Remarkably, many other studies have previously found either BZDs alone [ 28 30 ] or together with PPIs [ 4 , 12 , 31 33 ] among the most frequent PIMs.…”
Section: Discussionmentioning
confidence: 91%
“…An important finding of this study is that the most frequent active principles as PIMs, which were PPIs and BZDs, were present in almost half (46.6%) of the patients, suggesting that actions focused on deprescribing these medications may have a large impact on reducing PIP and, therefore, undesired negative outcomes. Remarkably, many other studies have previously found either BZDs alone [ 28 30 ] or together with PPIs [ 4 , 12 , 31 33 ] among the most frequent PIMs.…”
Section: Discussionmentioning
confidence: 91%
“…The number of PIMs identified varies among criteria, and in the inpatient setting, the prevalence of PIM changes from 1% to as high as 50% and is highly dependent on the tool used to define PIM (Franceschi et al, 2008;Rothberg et al, 2008;Page et al, 2010). A study carried out in Portuguese nursing homes and day-care centers detected a PIM prevalence of 64.4% when applying the EU( 7)-PIM list, 56% when applying the 2015 Beers criteria, and 85.5% when applying the STOPP v2 criteria (Monteiro et al, 2020). Another study carried out in Chinese inpatients reported a prevalence of PIM of 58.1 and 44.0% using 2015 Beers criteria and 2014 STOPP (Ma et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Prescribing tools such as Beers and STOPP/START criteria have been available for over a decade and have been integrated into computerized clinical decision support systems (CDSS). Prescribing tools have been successfully deployed to quantify the incidence of inappropriate prescribing but several studies over recent years, in a variety of clinical settings, have demonstrated that there is insufficient evidence of their clinical or economic impact 14,29‐33 . The failure of prescribing tools such as STOPP/START to reduce the incidence of inappropriate prescribing suggests that an alternative approach may be worthy of consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Prescribing tools have been successfully deployed to quantify the incidence of inappropriate prescribing but several studies over recent years, in a variety of clinical settings, have demonstrated that there is insufficient evidence of their clinical or economic impact. 14,[29][30][31][32][33] The failure of prescribing tools such as STOPP/START to reduce the incidence of inappropriate prescribing suggests that an alternative approach may be worthy of consideration. Hence, we propose that a greater understanding of factors that directly influence doctors during routine practice at the point of prescribing may help point the way towards providing better support for prescribers, including CDSS support, to ensure prescribing guidance translates into patient benefit.…”
Section: Discussionmentioning
confidence: 99%